Therapeutic cooling: No effect on hamstring reflexes and knee stability - Melnyk, M.; Faist, M.; Claes, L.; Friemert, B. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Stretch reflexes contribute to joint stiffness, but the effects of therapeutic cooling on these reflexes are unknown. Therapeutic cooling is frequently used in knee rehabilitation, for instance, after rupture of the anterior cruciate ligament. Cooling a joint can affect nerve conduction velocity and the function of sensory organs. Such changes in neuromuscular coupling could reduce knee stability and increase the risk of knee injury. The aim of the present study was to evaluate whether there are negative effects of knee cooling on the hamstring short and medium latency reflex responses or on the anterior tibia trajectory after mechanically induced tibia translation.